Perspective directions of experimental research on fundamental physics at intermediate energies on the proposed NSC KIPT 730 MeV linear electron accelerator - Ganenko, V.B.; Konovalov, O.G.; Korchin, A.Yu.; Maslov, N.I.; Shevchenko, N.G. (Вопросы атомной науки и техники, 2004)
Perspertive directions in fundamental nuclear and hadron physics with electromagnetic probes at intermediate energies up to 1 GeV are discussed. It is emphasized that for electron accelerator with the energy 500…730 MeV, duty factor ~1 and current up to 100 mkА, which is proposed at NSC KFTI there are following possible perspective topical trends which could be studied which will be; i) test of theoretical predictions of the chiral perturbation theory; ii) many-body processes and influence of nuclear medium on hadron properties; iii) test of the electroweak theory in scattering of polarized electrons on nucleons and nuclei, and the parity violation effects.